Motivasi, Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan (Studi pada PT. Angkasa Pura Logistik Semarang) - Nadila Meysa Putri; Sri Isnowati (IPM2KPE, 2024)
This research aims to determine the influence of motivation, communication and work discipline on employee performance. The object of this research is employees of PT. Angkasa Pura Logistics Semarang. The sample used in this research was 63 respondents using a saturated sampling technique. This type of research is a quantitative method. The data source in this research is primary data and data collection uses a questionnaire method. This data analysis method uses multiple linear analysis to test hypotheses through simultaneous hypothesis testing (F Test) and hypothesis testing (T Test). The results of this research show that motivation, communication and work discipline have a positive and significant effect on employee performance. Keywords: Work Discipline, Employee Performance, Communication, Motivation